Tigecycline therapy for carbapenem‐resistant Klebsiella pneumoniae (CRKP) bacteriuria leads to tigecycline resistance. (12th December 2014) - van Duin, D.; Cober, E. D.; Richter, S. S.; Perez, F.; Cline, M.; Kaye, K. S.; Kalayjian, R. C.; Salata, R. A.; Evans, S. R.; Fowler, V. G.; Bonomo, R. A.; Cantón, R.
Abstract Carbapenem‐resistant Klebsiella pneumoniae (CRKP) is an increasing global threat. Here, we describe the prevalence and impact of tigecycline use in a cohort of patients with CRKP bacteriuria nested within a multicentre, prospective study. In the 21‐month study period, 260 unique patients were included. Tigecycline was given to 80 (31%) patients. The use of tigecycline during the index hospitalization was significantly associated with the subsequent development of tigecycline resistance in the same patient (OR, 6.13; 95% CI, 1.15–48.65; p 0.03). In conclusion, the use of tigecycline with CRKP bacteriuria is common, and is associated with the subsequent development of tigecycline resistance.